The physiological effects of concurrent strength and endurance training sequence: A systematic review and meta-analysis - Murlasits, Z.; Kneffel, Z.; Thalib, L. (Journal of Sports Sciences, 2018)
We conducted a systematic literature review and meta-analysis to assess the chronic effects of the sequence of concurrent strength and endurance training on selected important physiological and performance parameters, namely lower body 1 repetition maximum (1RM) and maximal aerobic capacity (VO2max/peak). Based on predetermined eligibility criteria, chronic effect trials, comparing strength-endurance (SE) with endurance-strength (ES) training sequence in the same session were included. Data on effect sizes, sample size and SD as well other related study characteristics were extracted. The effect sizes were pooled using, Fixed or Random effect models as per level of heterogeneity between studies and a further sensitivity analyses was carried out using Inverse Variance Heterogeneity (IVHet) models to adjust for potential bias due to heterogeneity. Lower body 1RM was significantly higher when strength training preceded endurance with a pooled mean change of 3.96 kg (95%CI: 0.81 to 7.10 kg). However, the training sequence had no impact on aerobic capacity with a pooled mean difference of 0.39 ml/kg.min (95%CI: -1.03 to 1.81 ml/kg.min). Sequencing strength training prior to endurance in concurrent training appears to be beneficial for lower body strength adaptations, while the improvement of aerobic capacity is not affected by training order.